Pengaruh Model Problem Based Learning (PBL) Terhadap Karakter Disiplin Peserta Didik pada Mata Pelajaran PPKn UPTD SDN 119 Ir. Wasito Kabupaten Maros - Sri ayu ningsi; Jumiati Nur; Musdalifah Syahrir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model on the discipline character of students in the Civics (PPKn) subject at SDN 119 Ir. Wasito, Tompobulu District, Maros Regency. The study uses a quantitative approach with a quasi-experimental design and a one-group pretest-posttest design. The sample consisted of 11 fourth-grade students. Data were collected using a discipline character questionnaire, classroom observations, and documentation. Descriptive analysis revealed an increase in the average discipline score from 119.64 (pretest) to 149.55 (posttest). A paired-samples t-test showed a significance value of p = 0.000 (< 0.05), indicating that the application of the PBL model significantly improves students' discipline character. Therefore, the PBL model is recommended to be implemented as an alternative instructional strategy in Civics education to enhance character development in primary schools.